2021
DOI: 10.1002/trc2.12190
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Alzheimer's disease within reach by 2025: Targeted‐risk‐AD‐prevention (TRAP) strategy

Abstract: Introduction Alzheimer's disease (AD) is a progressive neurodegenerative disease that currently affects 6.2 million people in the United States and is projected to impact 12.7 million worldwide in 2050 with no effective disease‐modifying therapeutic or cure. In 2011 as part of the National Alzheimer's Project Act, the National Plan to Address Alzheimer's Disease was signed into law which proposed to effectively prevent AD by 2025, which is rapidly approaching. The preclinical phase of AD can begin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…MCI was divided into early mild cognitive impairment (EMCI) and late mild cognitive impairment (LMCI). Studies had pointed out that if MCI patients were not diagnosed early, the probability of developing AD could be as high as 80% after 6 years, and about two-thirds of AD patients were converted through MCI ( Barnes and Yaffe, 2011 ; Lenhart et al, 2021 ; Vitali et al, 2021 ). Using linear mixed models, Vonk et al (2020) analyzed 2,261 individuals with MCI and non-MCI and found that the neurodegeneration was associated with letter fluency and semantic fluency.…”
Section: Introductionmentioning
confidence: 99%
“…MCI was divided into early mild cognitive impairment (EMCI) and late mild cognitive impairment (LMCI). Studies had pointed out that if MCI patients were not diagnosed early, the probability of developing AD could be as high as 80% after 6 years, and about two-thirds of AD patients were converted through MCI ( Barnes and Yaffe, 2011 ; Lenhart et al, 2021 ; Vitali et al, 2021 ). Using linear mixed models, Vonk et al (2020) analyzed 2,261 individuals with MCI and non-MCI and found that the neurodegeneration was associated with letter fluency and semantic fluency.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple risk factors for AD can initiate or contribute to the preclinical stage of AD and ultimately result in AD if not effectively controlled [11]. Based on our Targeted-Risk-AD-Prevention (TRAP) strategy, 364 AD risk factors were identified with diabetes, dyslipidemia, hypertension, and inflammation as principle drivers [12]. These AD risk factors were associated with 629 FDA-approved drugs, 46 of which were identified as high confidence therapies to reduce the risk of AD [12].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that effective prevention will require predicting who will develop AD long before the onset of symptoms. Therefore, there is significant interest in identifying biomarkers for individuals at increased risk of AD, who can then be targeted with preventive interventions such as risk factor reduction, behavioural modification, and pharmacologic treatment [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%